Soviet Heavy Industry: A Dollar Index of Output, 1927/28-1937 - Gerschenkron, Alexander (The Review of Economics and Statistics, 1955)
THE purpose of this note is to communicate in summary form the results of an attempt to measure the growth of output in Soviet heavy industry. The study has been conducted at Harvard in the years I949-54 under the auspices of The RAND Corporation of Santa Monica, California. While the title chosen for this summary appeals to the author's ego, it is somewhat misleading. The underlying research did not cover the whole range of Soviet heavy industry. Most notably, production of heavy chemicals and of nonferrous metals has been entirely omitted. The investigation in its present form embraces the following five branches of industry: (i) machine-building, ( 2) iron and steel, (3) petroleum, (4) coal, and (5) electric power. Granted these limitations, it should be clear that the industries just mentioned, during the period under review, must have accounted for the bulk of the heavy industrial output in Soviet Russia. It should be remembered in particular that the concept of machinery used in this study is comprehensive indeed. In addition to industrial machinery proper, it includes railroad rolling stock, automotive production, and agricultural and road-building machinery.